Sustainability of E-Learning in the Undergraduate EFL Classrooms - Ferdous, Asmaul; Forhin Shifat, Nazia; Ehsanul Islam Khan, Mohammad (FOSTER: Journal of English Language Teaching, 2022)
The present study investigated the probable sustainability and effectiveness of e-learning in English language teaching (ELT) to learners in an English as a foreign language (EFL) classroom. Since the beginning of technology, it has always influenced our lives, thinking, and learning areas. One significant model in today's world in education is E-Learning. Today, one aspect of technology that has a considerable impact on our livelihood is English language learning in the EFL context. Data were collected using a Google form questionnaire with 20 close-ended questions with a 5-point Likert scale and analyzed in percentage. Ninety-two undergraduate EFL learners randomly participated in the survey. The quantitative method has been used to analyze the data. The results showed that integrating e-learning is a blessing to language learners though students face some challenges entirely using it. Learners have found educational technology effective in developing their fours language skills, including vocabulary problem-solving skills, performance improvement, etc. The study finally recommended increasing e-learning practices alongside the traditional approach in the EFL context of Bangladesh along with secured and controlled techniques.